INTERDISCIPLINARITY IN CONDITIONS OF MORPHO-PSYCHOLOGICAL RECORDS AND ANTHROPOMETRIC ANALYSIS IN PATIENTS WITH ALGO-DYSFUNCTIONAL SYNDROME AND MODERATE DEPRESSIVE DISORDERS - Lucian Stefan Burlea; Doriana Agop Forna; Veronica Serban Pintiliciuc; Tudor Hamburda; Ovidiu Stamatin; Liana Aminov; Bogdan Petru Bulancea; Laura Elisabeta Checherita (Romanian Society of Oral Rehabilitation, 2024)
Temporo-mandibular disorders (TMDs) represent a major cause of non-dental pain in the orofacial region, the effects of which may be presumed to form at the site where the greatest forces are exerted, and host resistance is least. The signs and symptoms of TMDs which are observed in patients with psychiatric easy disease observed and measured by anthropometrical methods and correct with specific treatment. The literature reviewed in the present work revealed that suggests a complex relationship between psychological status and treatment outcome and TMDs signs and symptoms in different groups of individuals persists and the specificity and morphological dates also. Timely identification and the management of this condition may improve the comfort and psychic status of the patients, underlined also in our research.